UPAYA PENINGKATAN KEMAMPUAN APARAT KECAMATAN DALAM PELAKSANAAN TUGAS ADMINISTRASI PEMERINTAH KECAMATAN MURUNG KABUPATEN MURUNG RAYA - Mila, Mila Rosa; Dra. Puput Ratnasari, M. Hum; Sri Mujiarti Ulfah, S.Sos. M.AP (Universitas Palangka Raya, 2020)
The problem in Murung Subdistrict is seen from the facilities and infrastructure, which will cause service to the community to be hampered and not maximal, so that the service in the sub-district is still complained by the community. For this reason, the purpose of service can truly be achieved as expected by the village community, so what must be considered is the presence of government officials who have adequate quality. The problem formula in this study is: